The Role of Gut Microbiota in Food Digestion and Its Implications for Human Health - Njoki , Phillis (Journal of Food Sciences, 2024)
Purpose: The general aim of this study was to examine the role of gut microbiota in food digestion and its implications for human health. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the role of gut microbiota in food digestion. Preliminary empirical review revealed that gut microbial communities play a dynamic role in modulating nutrient metabolism, immune function, and overall digestive wellness. Through diverse empirical investigations, it was revealed that gut microbiota composition is influenced by factors such as diet, lifestyle, and host genetics, with dysbiosis linked to immune-mediated gastrointestinal disorders. Moreover, dietary interventions and lifestyle modifications were identified as effective strategies for modulating gut microbiota composition and function, offering promising avenues for promoting digestive health. Overall, this research provided valuable insights into the complex interactions between gut microbiota and host physiology, paving the way for personalized therapeutic interventions to optimize digestive function and mitigate gastrointestinal disorders. Unique Contribution to Theory, Practice and Policy: The Ecological theory of Gut Microbiota, Metabolic theory of Gut Microbiota and Immunological theory of Gut Microbiota may be used to anchor future studies on the role of gut microbiota in digestion and its impacts on human health. The study provided recommendations that contributed to theory, practice, and policy in microbiome research and public health. It suggested further exploration of ecological theory to understand the dynamic interactions between gut microbiota and food digestion, leading to advancements in theoretical frameworks. Practically, the study emphasized personalized nutrition interventions based on gut microbiota composition to optimize digestive health, while policy recommendations included integrating microbial research into public health initiatives and fostering interdisciplinary collaboration. These recommendations aimed to translate microbiome science into actionable strategies for improving digestive health outcomes and enhancing overall well-being.